Fracture resistance of shape memory alloys under thermomechanical loading. (December 2021) - Makkar, J.; Young, B.; Karaman, I.; Baxevanis, T.
Abstract: Experimental measurements of the fracture resistance of Shape Memory Alloys (SMAs) under thermomechanical loading conditions are reported. NiTi compact tension specimens are subjected to either isothermal mechanical or isobaric thermal loading; the latter loading path is an idealization of typical loading paths that utilize these alloys as actuators. A single-parameter description of the experimental data is employed on the basis of a path-independent contour integral, which is approximated by the load–load-line displacement curves recorded from the experiments. The obtained results represent the first experimental measurement of the fracture toughness of SMAs under coupled thermo-mechanical loading, and indicate that the fracture toughness enhancement associated with crack advance under isobaric thermal loading is less pronounced than the corresponding one under isothermal mechanical loading. Graphical abstract: Highlights: A single-parameter description of the fracture toughness of SMAs is proposed. The fracture toughness of SMAs is measured from actuation loading experiments. The resistance to crack advance is more pronounced for isothermal loading than actuation loading.